Correlation Between Assembling to Order and Customer Satisfaction in the South African Automobile Supply Chain Industry - Polycarpe Feussi; Charles Mbohwa (Research Synergy Press, 2025)
Supply chain postponement research has mainly focused on inventory management and lead time. The South African car industry is vital for the economy, driving job creation and economic development, thus addressing social issues such as inequality, unemployment, and crime. It is essential to meet client needs and proactively plan for sector growth, as this will create new job opportunities, drive economic progress, and improve the overall quality of life. This study investigates the relationship between assembly and order (ATO) and customer satisfaction in the South African automobile supply chain. Through the administration of a cross-sectional survey incorporating closed-ended questions, we obtained quantitative data from a sample of 375 individuals working at automobile dealerships. This data was then analyzed to evaluate the hypothesis that the ATO strategy can enhance customer satisfaction. Embracing this research is not just beneficial; it is a necessary step toward elevating service quality and fostering industry advancement. The findings revealed that customer input through the process could potentially improve customer satisfaction by improving five service quality variables, namely the tangibles: responsiveness, empathy, assurance, and reliability. Key stakeholders in this supply chain segment must prioritize enhancing customer relationship management and gaining deeper insights into end customers. Using the customer decoupling point with assembly-to-order (ATO) processes, along with targeted marketing and thorough market research, can achieve this goal. Focusing on customer satisfaction fosters loyalty, leading to more efficient marketing and superior relationship tactics, ultimately boosting the South African automobile industry’s market share and positively impacting job preservation and creation.